Parenting Styles, Prosocial, and Aggressive Behavior: The Role of Emotions in Offender and Non-offender Adolescents - Llorca, Anna; Richaud, María Cristina; Malonda, Elisabeth (Frontiers in Psychology, 2017)
The aim is to analyse the parenting styles effects (acceptance, negative control and negligence) on prosociality and aggressive behavior in adolescents through the mediator variables empathy and emotional instability, and also, if this model fits to the same extent when we study adolescents institutionalised due to problems with the law and adolescents from the general population, and at the same time, if the values of the different analysed variables are similar in both groups of adolescents. We carried out a cross-sectional study. 220 participants from schools in the metropolitan area of Valencia took part in the study. Also, 220 young offenders took part recruited from four Youth Detention Centres of Valencia, in which they were carrying out court sentences. The age of the subjects range from 15-18 years. The results indicate that the emotional variables act as mediators in general, in the non-offender adolescents, but it has been observed, in the offender adolescents, a direct effect of support on aggressive behavior in a negative way and on prosociality in a positive way; and of negligence on aggressive behavior and of permissiveness on prosociality in a negative way.